The argentine dictionaries of barbarisms: glotopolytic analysis of the published between 1890 and 1903 - Lauria, Daniela (2020)
This article analyzes, from the glottopolitical approach, a series of four monolingual lexicographical works of the Argentine Spanish published between 1890 and 1903, which are grouped in the category "dictionaries of barbarisms". These are linguistic instruments that assume a prescriptive character since they include and, by extension, exclude certain uses and certain words, as well as describing, qualifying and evaluating the lexical differences between the American (the Argentine case in particular) and the Peninsular use in the moment of greatest boom of the massive migratory movement that entered the country. Broadly speaking, they register barbarisms, neologisms and foreign words and censure their use, taking as a parameter the norm of the Madrid Castilian. Here it is argued that these devices expose value systems and dominant conceptions of the language, which far exceed the strictly linguistic scope.